Intrathecally Administered Apelin-13 Alleviated Complete Freund's Adjuvant-Induced Inflammatory Pain in Mice - Shuangyu Lv; Xiaomei Zhang; Yuchen Zhou; Yu Feng; Yanjie Yang; Xinchun Wang (Frontiers Media S.A., 2020)
Apelin is the endogenous ligand for APJ, a G-protein-coupled receptor. Apelin gene and protein are widely distributed in the central nervous system and peripheral tissues. The role of apelin in chronic inflammatory pain is still unclear. In the present study, a mouse model of complete Freund's adjuvant (CFA)-induced inflammatory pain was utilized, and the paw withdrawal latency/threshold in response to thermal stimulation and Von Frey ﬁlament stimulation were recorded after intrathecal (i.t.) injection of apelin-13 (0.1, 1, and 10 nmol/mouse). The mRNA and protein expression, concentration of glutamic acid (Glu), and number of c-Fos immunol staining in lumbar spinal cord (L4/5) were determined. The results demonstrated that Apln gene expression in the lumbar spinal cord was down-regulated in the CFA pain model. Apelin-13 (10 nmol/mouse, i.t.) alleviated CFA-induced inflammatory pain, and it exhibited a more potent antinociceptive effect than apelin-36 and (pyr)apelin-13. The antinociception of apelin-13 could be blocked by APJ antagonist apelin-13(F13A). I.T. apelin-13 attenuated the increased levels of Aplnr, Grin2b, Camk2d, and c-Fos genes expression, Glu concentration, and NMDA receptor 2B (GluN2B) protein expression caused by CFA. Apelin-13 significantly reduced the number of Fos-positive cells in laminae III and IV/V of the dorsal horn. This study indicated that i.t. apelin-13 exerted an analgesic effect against inflammatory pain, which was mediated by activation of APJ, and inhibition of Glu/GluN2B function and neural activity of the spinal dorsal horn.